Gestão por competência: análise de modelos e aplicações em bibliotecas universitárias federais - Flores, Michelle (2021)
The present research proposal analyzed the management models applied in Federal University Libraries comparing them with the Competency Management model, highlighting the pros and cons after their implementation by the managers. The objective was also to propose suggestions for a possible Competency Management model to be implemented in Federal University Libraries. The research is qualitative, quantitative, descriptive and exploratory. A structured questionnaire was applied to managers and administrative documents from the Federal University Libraries surveyed were also analyzed. 34 of the 65 questionnaires sent were answered, corresponding to 52.30%, and the documents of these libraries were analyzed. The analysis of qualitative data was performed according to Bardin's Content Analysis (1977) and for closed questions, the analysis of quantitative data was used. The analysis of administrative documents verified the indicators of organizational and individual competencies present in the documents and in the practice of library management. The Organizational Indicators: Strategic Planning, Mission, Vision and Values, Mapping Competencies and People Management. Individual Indicators: Training and Development Program, Career Plan and Performance Evaluation. With the analysis it was realized that Management by Competence is a subject of knowledge and interest of managers, and that 100% of libraries have part or total of the Management by Competence model applied, thus evidencing the importance of the model for the University Libraries. The importance of drafting administrative documents was also noted in the research, with Strategic Planning and the definition of Mission, Vision and Values being observed in 20 and 24 libraries, respectively, of the 34 surveyed, as well as the Competency Mapping, a fundamental process in KM is not a practice in management, only 9 libraries do this mapping. The indicators, Performance Evaluation and Career Plan were observed in all libraries, as they are federal institutions, and have the TAEs Career Plan, in accordance with Law 11.091, of 12/01/2005. The negative points pointed out were, difficulties in the implementation of the Competency Management model, in the participation of civil servants, in the relocation, and in the implementation of the model in public agencies and civil servants without training. The positive points were, identification of individual skills, job satisfaction, collaborative environment. The analysis of the products and services offered showed that there is a standardization of these, but some differentiated products and services were identified, such as: services and products for people with disabilities, film exhibition and exhibition of arts and culture, tutorials, ISBN request, ISSN and DOI, copyright request. Faced with the reality found in Federal University Libraries and the interest of some managers in getting to know the subject better and even implementing the Competency Management model in their library, suggestions were made for the implementation of a possible Competency Management Model in Libraries Federal University Universities, which includes 3 stages: I. Presentation, II. Competency Mapping and III. Evaluation and Evolution, detailing the procedures foreseen in the implantation.